THE THERAPEUTIC TACTICS OF INTRA-ARTICULAR FRACTURES OF THE ANKLE (LITERATURE REVIEW) - I. V. Zedgenidze (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
As a result of the analysis of literature it was revealed that in case of pronation-abduction ankle injury takes place injury of the articular surfaces. The hyaline cartilage significantly suffers. Typical localization of damage of the articular cartilage is the middle or front third of the inner edge of talus block. The damage can spread to articular surface of the outer block of the talus. In 50 % cases the articular cartilage is the front edge of the tibia is damaged. The combination of damages of the articular cartilage of the inner edge of the block of the talus and the outside the department anterior edge of the tibia is more often (from 43 % till 57 %). In 80 % cases the damage of the articular cartilage surface of the talus ankle as roughness, cracks, defects with exposure of subchondral bone was revealed. The results say that in case of damage bony and ligamentous structures of the ankle at the joint pronation-abduction mechanism the articular cartilage significantly suffers. The size and character of the damages of the articular cartilage differs. i4s a result we can say that initially severe damage of the articular cartilage at trauma will significantly worsen the immediate and long-term results and this fact should be taken into account while making plan of the treatment of patients with ankle injury.